Safety assessment of the process 'BTB PET DIRECT IV* +', used to recycle post‐consumer PET into food contact materials. (19th April 2018) - ,; Silano, Vittorio; Bolognesi, Claudia; Castle, Laurence; Chipman, Kevin; Cravedi, Jean‐Pierre; Engel, Karl‐Heinz; Fowler, Paul; Franz, Roland; Grob, Konrad; Gürtler, Rainer; Husøy, Trine; et al.
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety evaluation of the recycling process BTB PET direct IV+ (EU register number RECYC0152). The input of the process is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer food contact PET containing no more than 5% of PET from non‐food consumer applications. In this technology, washed PET flakes are extruded into pellets which are further crystallised. Crystallised pellets are then preheated and fed to the solid‐state polycondensation (SSP) reactor. Having examined the challenge test provided, the Panel concluded that extrusion, crystallisation and SSP are the critical steps that determine the decontamination efficiency of the process. The operating parameters that control their performance are well defined and they are temperature, pressure and residence time. Under these conditions, it was demonstrated that the recycling process is able to ensure that the level of migration of potential unknown contaminants into food is below the conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process, intended to be used up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature, with or without hotfill, is not considered of safety concern. Trays made of this recycled PET are not intended to be used, and should not be used, in microwave and conventional ovens.